2022
DOI: 10.1128/aac.01732-21
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Clinical Trial to Assess the Safety, Tolerability and Pharmacokinetics of Single Doses of NTM-1633, a Novel Mixture of Monoclonal Antibodies against Botulinum Toxin E

Abstract: Botulism is a rare, life-threatening paralytic disease caused by botulinum neurotoxin (BoNT). Available treatments including an equine antitoxin and human immune globulin are given postexposure and challenging to produce and administer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Such antibodies can be GMP manufactured and combined as three-mAb combinations. When studied in Phase 1 clinical trials, they showed no serious drug-related adverse events for mAb combinations against serotype A [ 24 ], serotype B [ 25 ], serotypes C and D [ 26 ], or serotype E [ 27 ]. In contrast, the current FDA-approved therapy, equine-derived BAT ® [ 20 ] is immunogenic, and hypersensitivity reactions have been reported, including cardiac arrest and serum sickness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such antibodies can be GMP manufactured and combined as three-mAb combinations. When studied in Phase 1 clinical trials, they showed no serious drug-related adverse events for mAb combinations against serotype A [ 24 ], serotype B [ 25 ], serotypes C and D [ 26 ], or serotype E [ 27 ]. In contrast, the current FDA-approved therapy, equine-derived BAT ® [ 20 ] is immunogenic, and hypersensitivity reactions have been reported, including cardiac arrest and serum sickness.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we have developed safe and effective monoclonal antibody (mAb) based countermeasures for BoNT/A, B, C, D, and E, which have all completed Phase 1 clinical trials with no drug-related serious adverse effects [ 24 , 25 , 26 , 27 ] and have developed a recombinant mAb-based antitoxin for BoNT/F which is in preclinical development [ 28 ]. In the current work, we report the identification of mAbs against BoNT/G that, when combined, potently neutralize BoNT/G and thus could be used in the diagnosis, prevention, and treatment of BoNT/G-induced botulism.…”
Section: Introductionmentioning
confidence: 99%
“…В данном исследовании было показано, что период полувыведения препаратов антител составляет в среднем от 6,5 до 10 суток. Позднее с использованием данных антител был произведен ряд экспериментальных исследований по оценке их протективной эффективности на животных моделях, а также клинические исследования по оценке фармакокинетических характеристик, которые показали их высокую эффективность и безопасность [17][18][19][20][21].…”
Section: Biological Security and Protection Against Biological Threat...unclassified
“…Genetically engineered monoclonal antibodies are also in the development stage (Raja et al 2022;Rasetti-Escargueil et al 2017;Tomic et al 2021). However, technologically, equine-derived BAT is the most mature BAT available to date (Kim et al 2019;Rasseti-Escargueil and Popoff 2019;Richardson et al 2020).…”
Section: Introductionmentioning
confidence: 99%